Quantitative threat situational assessment method for higher secure attribute value device - Lei HAN; Jiqiang LIU; Jian WANG; Bo SHI; Xudong HE (网络与信息安全学报)
Traditional network security situational assessment is mainly for the macro network security situation， not for the specific equipment,especially for the key network device.A conception about the higher secure attribute value device was introduced,based on which a threat situational assessment research framework was presented and assessment indexes were discussed.A quantitative threat situational assessment method for higher secure attribute value device was proposed based on assessment research framework and assessment indexes.The experiment resultsshow that the proposed method can assess device threat situation accurately and effectively.Meanwhile,the method is more general and objective than traditional methods.